Bokrecension: Why Students Resist Learning. A Practical Model for Understanding and Helping Students - Jenny Katarina Eklöf (Högre Utbildning, 2018)
Why Students Resist Learning: A Practical Model for Understanding and Helping Students. Redigerad av Anton O. Tolman och Janine Kremling. Stylus Publishing, Llc., 2017